Research on Classroom Assessment Practices: A Literature Review - Felipe Martínez Rizo; Adriana Mercado Salas (Universidad Autónoma de Baja California, 2014)
Some efforts to improve the quality of education are based on the idea that students' performance improves if the teacher uses formative assessment, although the related research is not conclusive. However, in these studies assessment has often been characterized as formative or not based only on the presence or absence of previously specified behaviors, thus failing to take into account more subtle aspects such as the level of cognitive demand of the contents or how feedback is provided. This paper summarizes results from some of the very few studies that have specifically sought to examine the classroom assessment practices of teachers in detail. The results will guide the design of instruments that will allow the gathering of better quality information on teachers' assessment practices, which is the aim of this line of research.